Genotype–Phenotype Analysis of RPGR Variations: Reporting of 62 Chinese Families and a Literature Review - Yang, Junxing; Zhou, Lin; Ouyang, Jiamin; Xiao, Xueshan; Sun, Wenmin; Li, Shiqiang; Zhang, Qingjiong (Frontiers in Genetics, 2021)
Purpose: RPGR is the most common cause of X-linked retinitis pigmentosa (RP), of which female carriers are also frequently affected. The aim of the current study was to explore the RPGR variation spectrum and associated phenotype based on the data from our lab and previous studies. Methods: Variants in RPGR were selected from exome sequencing data of 7092 probands with genetic eye diseases. The probands and their available family members underwent comprehensive ocular examinations. Similar data were collected from previous reports through searches in PubMed, Web of Science, and Google Scholar. Systematic analyses of genotypes, phenotypes and their correlations were performed. Results: A total of 46 likely pathogenic variants, including nine missense and one in-frame variants in RCC1-like domain and 36 truncation variants, in RPGR were detected in 62 unrelated families in our in-house cohort. In addition, a total of 585 variants, including 491 (83.9%) truncation variants, were identified from the literature. Systematic analysis of variants from our in-house dataset, literature, and gnomAD suggested that most of the pathogenic variants of RPGR were truncation variants and pathogenic missense and in-frame variants were enriched in the RCC1-like domain. Significant different phenotypes were present between males and female carriers, including more severe refractive error but better best corrected visual acuity (BCVA) in female carriers than those in males. The male patients showed a significant reduction of BCVA with increase of age and males with exon1-14 variants presented a better BCVA than those with ORF15 variants. For female carriers, the BCVA also showed significant reduction with increase of age, but BCVA in females with exon1-14 variants was not significant difference compared with those with ORF15 variants. Conclusions: Most pathogenic variants of RPGR are truncations. Missense and in-frame variants located outside of the RCC1-like domain might be benign and the pathogenicity criteria for these variants should be considered with greater caution. The BCVA and refractive error are different between males and female carriers. Increase of age and location of variants in ORF15 contribute to the reduction of BCVA in males. These results are valuable for understanding genotypes and phenotypes of RPGR.